Investors' and Central Bank's Uncertainty Embedded in Index Options - David, Alexander; Veronesi, Pietro (Review of Financial Studies, 2014)
Shocks to equity options' implied volatility are followed by persistently lower short-term rates. Shocks to puts' over calls' out-of-the-money implied volatilities (P/C) are followed by persistently higher rates. Stock and Treasury bond implied volatilities, which measure market and policy uncertainty, are countercyclical, while P/C, which measures downside risk, is procyclical. An equilibrium model in which investors and the central bank learn about composite regimes of economic and policy variables explains these dynamics, linking them to a learning-based, forward-looking Taylor rule. Survey data support our model's predictions on the effect of uncertainty on the level and fluctuations of implied volatilities.